Expectations and the Demand for Agricultural Loans - Yusoff, Mohammed; Habibullah, Muzafar Shah (1990)
The demand for agricultural loans incorporating price expectations was formulated and estimated in this study. All equations estimated indicate that the interest rate is not an important determinant of the demand for agricultural loans. But other variables such as price of output, assets and acreage are significant at 5 percent level, except for rubber and oil palm. In the rubber equation, only the price and acreage are significant, while in the oil palm equation, only the acreage is significant. The results suggest that the naive expectations model is good enough to explain the behaviour ofthefarmers in Malaysian agricultural loans market.